Daily activity rhythm of sympatric ungulate species in Fanjingshan Reserve, China - Dan Xiang; Bingshun Meng; Bo Xie; Xiaolong Huang; Cheng Wang; Jingcheng Ran; Haijun Su; Mingming Zhang (Global Ecology and Conservation, 2024)
Sympatric species inhabiting similar ecological niches can coexist by partitioning aspects of available ecological resources, such as temporal, spatial, and nutritional niches. Ungulates often coexist in the same habitat, resulting in temporal partitioning and divergence in foraging strategies and spatial utilization. To understand the temporal patterns of ecological differentiation and coexistence mechanisms among sympatric ungulates, we analyzed the monitoring data in Fanjingshan National Nature Reserve, Guizhou, China, from 2017 to 2022. Kernel density estimation was used to scrutinize disparities in diurnal activity patterns among four ungulates [tufted deer (Elaphodus cephalophus), Reeves' muntjac (Muntiacus reevesi), wild boar (Sus scrofa), and mainland serow (Capricornis milneedwardsii)] as well as the interspecies variances during different seasons, at diverse altitudes, and between breeding and non-breeding periods. Daily activity patterns differed significantly among four species, with those of tufted deer, Reeves' muntjac, and wild boar affected significantly by season and breeding cycle. In addition, the daily activity rhythms of four species were affected by altitude. Thus, the daily activity rhythms of these ungulates were resulted from a combination of environmental factors and interspecific competitive interactions, as well as the reproductive cycle of each species. Our results provided a scientific reference for the effective management of wildlife and forest ecosystems, and we suggest that knowledge of temporal dynamics should be integrated into conservation planning for these sympatric species.